KORUPSI : KERIKIL TAJAM DALAM SEPATU GOOD GOVERNANCE - Muslimin . (REFORMASI, 2015)
Corruption is a disease that disrupt and damage mechanisms of public administration. The phenomenon of corruption has made public service misdirected, wasteful, increasing poverty, thwarted welfare programs, making deforestation, courts without justice, and affect the relationship between the elite with the masses into gaps, leaders do not aspirational and not responsive to the public interest, as well as the social system becomes selfish individuals in society into mutual distrust and mutual suspicion, competition in the pursuit of economic values become unhealthy. And corruption in Indponesia already in the most acute stage, at least it has been shown by the data of Transparency International survey last few years Indonesia ranks as the most corrupt country in the world. Despite the Anti-Corruption Commission has been established and has managed to imprison corrupt officials, both at central and local levels, but corruption continues to increase. Diverse forms of corruption have, first, the daily petty corruption that became a habit in the environment of government employees, conducted when spending public money for purposes publk services, for example, a copy of the document, meubelair shopping, and so on which of the funds is not how. The second intermediate corruption, embezzled funds fairly dozens to tens of millions, occurs in mid-level officials. And are often carried out by private parties who carry out government projects, such as building rural roads or district. The impact on the quality of roads or buildings to be bad. The third high-level corruption involving officials of the minister or the governor doing my level of cooperation with the private sector in the implementation of the procurement of goods and services.